Решение задачи о построении линейной мозаики - Донец, Г.А.; Самер И.М. Альшаламе (Теорія оптимальних рішень, 2005)
For the first time, the problem of sample – aided imagery construction on a rectangular field is studied in this paper. Cases of different linear samples are analyzed in succession; necessary and sufficient conditions are found for a set of samples to be a basis for certain system of linear equations. Both one – colored and multi – colored samples are treated.